Transformation of siwa-sisya relationship within Hindu religiosity: Religious practices in the globalization era - Kumbara, A.A. Ngurah Anom; Wiasti, Made; Dewi, A.A. Sagung Kartika (International journal of linguistics, literature and culture, 2018)
Through globalization, the ideology of capitalism, with its belief in the free market system and rationalism is spread out throughout the world. This has risen up a crucial phenomenon not only to the transformation of socio-economic aspects but also to transformations of religiosity. In Bali, Indonesia, there has been a transformation of the Siwa-sisya or patron-client relationship, which is an integral part of the religiosity of Bali Hindus. Traditionally, Siwa resembles to be Pedanda or Pastors from the Brahmana background and sisya is the congregants of the respective Pastors which form a classic patron-client relationship. This research aims at analyzing and explaining the patron-client relationship transformation in Bali and its implications within Hindus practices. By applying a critical ethnography approach, the data was collected through observation, in-depth interview, and literature review. The data was analyzed qualitatively through three interrelated stages, namely data reduction, data presentation, and drawing conclusions or verification. The study reveals that there has been a shift of meaning from Siwa to Sulinggih, in which sisya now a freedom to choose Pastor has based on the market mechanism, which has resulted in a reformulation of the patron-client relationship. Consequently, Sulinggih can be Pastors even though the Pastors come from the non-Brahmana background. Therefore, such a relationship transformation can imply to the personalization of religion, the emergence of internal friction within Hindu communities, and contestation between Pedanda and Sulinggih in attracting sisya or clients on the basis of social capital, economic and symbolic power.